Macrophage migration inhibitory factor (MIF) in seminal ﬂuid as a marker of male factor infertility: a pilot study in Sri Lankan men - Obeysekera, Maheshi P.; Amarasekara, Dulshara S.; Wijerathna, Sumedha; Fernando, Chandrika; Udagama, Preethi V. (Journal of National Science foundation Sri Lanka, 2014)
Recent clinical and epidemiological studies worldwide suggest an increasing incidence of male factor infertility (MFI). Paucity of information on the biochemical analysis of seminal ﬂuid in Sri Lanka prompted undertaking a pilot study to establish a clinical marker for the male fertility status in Sri Lanka based on the level of the cytokine, macrophage migration inhibitory factor (MIF) in seminal ﬂuid, an area hitherto unexplored locally. The analysis was carried out on the semen samples of infertile males (N = 61) where age matched individuals (N = 30) with proven past paternity served as controls. D-dopachrome tautomerase assay was performed to assess the MIF level in semen while other seminal ﬂuid parameters were assessed according to the standard WHO criteria. The present study revealed an abnormal biphasic proﬁle of MIF in the seminal ﬂuid of individuals with impaired sperm parameters, which was either signiﬁcantly below or above the range of MIF tautomarase activity typical of normal fertile men (p < 0.000). This is the ﬁrst report in Sri Lankan population. The receiver operating characteristic (ROC) plot analysis established a cutoff point of 3.375 µg MIF/mL of semen (at 90 % sensitivity: 81.2 % speciﬁcity; 0.923 accuracy) to differentiate fertile from infertile males (excluding azoospermics and severe oligozoospermics). The MIF concentrations signiﬁcantly correlated with the semen pH in the azoospermic and severe oligozoospermic group. As MIF was clearly indicative of the male fertility status by estimates of sensitivity and speciﬁcity of the D-dopachrome tautomerase assay, MIF may be developed as a potential marker of male infertility in Sri Lanka
Keywords: severe oligozoospermia; Azoospermia; biphasic MIF proﬁle; D-dopachrome tautomerase assay; macrophage migration inhibitory factor (MIF); male factor infertility (MFI)